Implementasi UU Perlindungan Saksi dan Korban di Kota Gorontalo - Weny Almoravid Dunga (Fakultas Hukum Universitas Gadjah Mada, 2009)
The success or the opposite of a law affair handled is highly influenced by the evidence of presented witness in the related affairs. Considering how important the position of witness report is, so It is not impossible if a law affair failed within the process caused by the absence of supporting witness upon the affair. Being witness is an obligation which is obliged within our either acts or law system, because the witness saw, heard, experienced an event. But unfortunately, the obligation which is strongly recommended within either acts or law system do not always cause our society give the information of what they saw, heard, and witnessed to a crime action. Within various regulations which have ever been existing so far, in fact, eye witness some times in the unlucky position. The protection of eye witness is clearly required to give any guarantee and the law assurance for eye witness who posses’ bravery to open any cases. The aim of the acts protection of eye witness, is not only to protect, but also to increase the effectives in the law enforcement, primarily, the accomplishment of human right breaking law and corruptions. The existence of eye witness protection boards in the future will be influenced by things, such as: first, act regulations, second, the eye witness’ mentality attitude and victims. Third, the professionalism of law officers, fourth, society control, fifth; existence of electronic and press media.